Soluble ceramic shell / core and preparation method and application thereof
By adopting the droplet jet bonding molding process and modified CaO materials, soluble ceramic shells/cores are prepared, which solves the interfacial reaction and removal difficulties of existing ceramic shells/core materials in titanium alloy casting, and realizes the automatic separation of ceramic shells/cores and the satisfaction of industrial production needs.
Patent Information
- Application Number
- CN202510022319.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The existing ceramic shell/core materials have an interface reaction in titanium alloy casting, which affects the accuracy and performance of the casting. The materials are expensive and difficult to remove, making it difficult to achieve powder bed 3DP printing.
A soluble ceramic shell/core based on droplet jet bonding is used, and a modified CaO material is used to obtain modified calcium oxide powder by ball milling and drying of the modified solution. The ceramic shell/core is printed and sintered by droplet jetting technology.
The automatic separation of ceramic shell/core and castings is realized, the shelling process is simplified, and the production cost is reduced. The sintered ceramic shell/core shrinks and deformation is smaller, meeting industrial production needs.
Smart Images

Figure CN119794264A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field related to rapid casting, and in particular to a soluble ceramic shell / core and a preparation method and application thereof. Background Art
[0002] 3DP molding technology is a method of additive manufacturing. It is based on the powder bed process. The ink nozzle is used to select areas to spray the binder layer by layer on the powder bed. The layers are stacked to form a green part. The subsequent curing, infiltration, degreasing, and sintering processes are used to densify the parts and obtain parts with good mechanical properties. Compared with other additive manufacturing technologies, 3DP technology does not require laser or auxiliary heating molding. It has the advantages of a wide range of materials, high efficiency, low cost, no support, and green environmental protection. It has a wide range of applications and has great potential for preparing ceramic shells / cores.
[0003] Traditionally, the materials suitable for ceramic shells / cores for titanium alloy casting mainly include ZrO2, Y2O3, CaO, etc. The main advantage of these materials is that they can avoid interfacial reactions with titanium alloys during pouring, which affects the accuracy and performance of the castings. However, ZrO2 and Y2O3 are expensive, which greatly increases the production cost, and it is difficult to remove the ceramic shells / cores after pouring; although the CaO shells / cores can be hydrolyzed and deshelled, it is difficult to achieve powder bed 3DP printing due to the characteristics of CaO materials that easily absorb water and agglomerate in the air. Therefore, it is urgent to develop a method for preparing soluble ceramic shells / cores to solve the problems existing in the above-mentioned preparation technology and ceramic shell / core materials and meet the needs of industrial production. Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a soluble ceramic shell / core based on droplet jet bonding molding and its preparation method and application. The ceramic shell / core material adopts CaO, which is directly dissolved with water, and the ceramic shell / core will collapse and be easily separated from the casting, which greatly simplifies the later shelling process. The solubility of the dissolved product Ca(OH)2 is relatively small, and most of it will form a precipitate, which is convenient for later recycling. Since the present invention modifies CaO, the printing problem caused by powder agglomeration in the process of droplet jet bonding molding is optimized, and CaO will not decompose during the sintering process. The shrinkage deformation of the ceramic shell / core after sintering is relatively small, which can meet the needs of industrial production.
[0005] The technical solution of the present invention is implemented as follows: The present invention provides a method for preparing a soluble ceramic shell / core, the preparation method comprising the following steps:
[0006] Step S1: ball-milling, drying, and sieving the raw materials containing calcium oxide and modified solution to obtain modified calcium oxide powder;
[0007] Step S2: printing the modified calcium oxide powder into a ceramic shell / core blank, heating and curing, infiltration, and drying to obtain a ceramic shell / core blank;
[0008] Step S3: sintering the ceramic shell / core blank to obtain the soluble ceramic shell / core.
[0009] On the basis of the above technical solution, preferably, in the step S1, the modified solution includes a modifying agent and a modifying solvent.
[0010] On the basis of the above technical solution, preferably, the modifier is selected from at least one of ethyl bromide, benzene bromide, a silane coupling agent, stearic acid, and n-octadecyltrichlorosilane.
[0011] On the basis of the above technical solution, preferably, the modified solvent is selected from at least one of methanol, ethanol, glycerol and acetone.
[0012] On the basis of the above technical solution, preferably, the amount of the modifier is 1 to 10 parts by mass, and the amount of the modified solvent is 90 to 99 parts by mass.
[0013] On the basis of the above technical solution, preferably, the amount of the modifier is independently selected from any value of 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 8 parts, 10 parts or a range between any two of the above parts by mass.
[0014] On the basis of the above technical scheme, preferably, the amount of the modified solvent is independently selected from any value among 99 parts, 98 parts, 97 parts, 96 parts, 95 parts, 94 parts, 92 parts, 90 parts or a range value between any two of the above parts by mass.
[0015] On the basis of the above technical solution, preferably, in the step S1, the amount of calcium oxide used is 30 to 70 parts by mass, and the amount of the modified solution used is 70 to 30 parts by mass.
[0016] On the basis of the above technical solution, preferably, in step S1, the amount of calcium oxide is independently selected from any value of 30 parts, 40 parts, 50 parts, 60 parts, 70 parts by mass or a range between any two of the above.
[0017] On the basis of the above technical solution, preferably, in the step S1, the amount of the modified solution is independently selected from any value of 70 parts, 60 parts, 50 parts, 40 parts, 30 parts by mass, or a range between any two of the above.
[0018] On the basis of the above technical solution, preferably, in the step S1, the ball milling time is 6 to 12 hours.
[0019] On the basis of the above technical solution, preferably, during the ball milling, the diameter of the grinding balls is 0.8-2 mm.
[0020] On the basis of the above technical solution, preferably, during the ball milling, the mass fraction of the grinding balls is 5-15% of the raw material.
[0021] On the basis of the above technical solution, preferably, the drying temperature is 50-100° C., and the drying time is 6 h to 24 h.
[0022] On the basis of the above technical solution, preferably, when sieving after drying, the mesh number of the sieve is 100 to 500 meshes.
[0023] On the basis of the above technical solution, preferably, in the step S2, the temperature of the heating and curing is 150° C. to 180° C., and the time of the heating and curing is 2 h to 5 h.
[0024] On the basis of the above technical solution, preferably, the drying temperature is 50° C. to 90° C., and the drying time is 8 h to 24 h.
[0025] On the basis of the above technical solution, preferably, the impregnation time is 30s to 3min.
[0026] On the basis of the above technical solution, preferably, in the step S2, the impregnation liquid used in the impregnation is selected from at least one of nano-SiO2 ethanol dispersion, nano-ZrO2 ethanol dispersion and nano-YiO2 ethanol dispersion.
[0027] On the basis of the above technical solution, preferably, in the step S2, the printed layer height is 0.05 mm to 0.20 mm.
[0028] On the basis of the above technical solution, preferably, the printed binder is phenolic resin, and the saturation of the binder is 70% to 140%.
[0029] On the basis of the above technical solution, preferably, in the step S3, the sintering includes a first sintering and a second sintering.
[0030] On the basis of the above technical solution, preferably, the temperature of the first sintering is 600° C. to 800° C., and the time of the first sintering is 1 h to 3 h.
[0031] On the basis of the above technical solution, preferably, the temperature of the second sintering is 1300° C. to 1500° C., and the time of the second sintering is 2 h to 3 h.
[0032] On the basis of the above technical solution, preferably, the heating rate of the sintering is 1 to 5° C. / min.
[0033] According to another aspect of the present application, a soluble ceramic shell / core prepared by the above-mentioned preparation method is provided.
[0034] According to another aspect of the present application, there is provided an application of the above-mentioned soluble ceramic shell / core in a cast structure, wherein the material of the cast structure is selected from at least one of cast iron, cast steel, aluminum alloy, titanium alloy, and magnesium alloy.
[0035] On the basis of the above technical solution, preferably, after the pouring is completed, the structural part with the ceramic shell / core is placed in water, and the ceramic shell / core reacts with water to crack and disintegrate, and is separated from the structural part, thus completing the shelling process.
[0036] As an optional implementation mode, the present invention is implemented by the following technical solution:
[0037] The method for preparing the soluble ceramic shell / core of the present invention comprises the following steps:
[0038] (1) firstly, by weight, mix 1 to 10 parts of a modifier and 99 to 90 parts of a modifying solvent, heat in a water bath at 40 to 80° C. for 1 to 4 hours, and mix them evenly to obtain a modified solution; add 30 to 70 parts of calcium oxide, 70 to 30 parts of the modifying solution and ball milling beads into a ball milling jar, perform ball milling using a planetary ball mill, and then dry the ball milled uniform slurry, and sieve through a mesh to obtain a modified calcium oxide powder;
[0039] (2) using modified calcium oxide powder as a raw material, a ceramic shell / core blank is prepared by a droplet jet bonding molding process, and then heated and cured, impregnated with an impregnation liquid and completely dried to obtain a ceramic shell / core blank;
[0040] (3) Designing a sintering temperature curve, and sintering the ceramic shell / core blank obtained in step (2) to obtain the soluble ceramic shell / core.
[0041] Based on the above technical solution, preferably, the modifier can be decomposed before sintering in the first stage of sintering.
[0042] On the basis of the above technical solution, preferably, the binder used in the micro-droplet jetting bonding molding process is phenolic resin; the printing parameters are: printing layer height 0.05mm-0.20mm, adhesive saturation 70%-140%.
[0043] In the present invention, the solute molecules in the impregnation solution used for the impregnation do not decompose above 1500°C; the solute components of the impregnation solution will not react with the structural parts during the pouring process; the impregnation solution is used to penetrate into the pores between the calcium oxide powders, keep the shape of the ceramic shell / core intact, avoid the collapse of the green body during the sintering process, and enhance the strength of the green body after sintering. In the present invention, the impregnation solution is used to penetrate into the pores between the calcium oxide powders, keep the shape of the ceramic shell / core intact, avoid the collapse of the green body during the sintering process; the solute molecules in the impregnation solution can react with calcium oxide to enhance the strength of the sample after sintering; the solute components of the impregnation solution will not react with the structural parts during the pouring process. After the pouring is completed, the structural part with the ceramic shell / core is placed in water, and the calcium oxide in the ceramic shell / core reacts with water to cause the ceramic shell / core to crack and disintegrate, separate from the structural part, and complete the shelling.
[0044] In the present invention, calcium oxide is modified by using a modified solution, the solution is evenly mixed by ball milling and dried, and after the solvent evaporates, the modifier is fully coated on the surface of the CaO powder, reducing the contact between CaO and air, and reducing the influence of denaturation and agglomeration during the printing process on the final printing quality.
[0045] The soluble ceramic shell / core of the present invention has the following beneficial effects compared with the prior art:
[0046] (1) The present invention adopts a micro-droplet jet bonding molding process to prepare a ceramic shell / core, which can solve the limitations of traditional processes in molding large and complex structure ceramic shells / cores, shorten the production cycle, reduce production costs, and meet the production needs of the social market. At the same time, compared with other additive manufacturing technologies, the micro-droplet jet bonding molding process does not require laser or auxiliary heating molding, has the advantages of a wide range of materials, high efficiency, low cost, no support in the molding process, and green environmental protection, and has a wide range of applications.
[0047] (2) The ceramic shell / core prepared by the present invention using modified CaO has low raw material price. Since CaO can react with water, the casting with the ceramic shell / core can be fully immersed in hot water. The ceramic shell / core is hydrolyzed and disintegrated in water, and the ceramic shell / core and the casting are automatically separated, which greatly simplifies the subsequent shelling process. The process of dissolving the CaO ceramic shell / core is as follows:
[0048] CaO+H2O=Ca(OH)2
[0049] The solubility of the reaction product Ca(OH)2 is relatively low, and its solubility decreases with increasing temperature. Therefore, most of the Ca(OH)2 will form a precipitate, which is convenient for subsequent recovery and treatment. It is green and environmentally friendly, and has broad application prospects.
[0050] (3) The present invention adopts ball milling and modifier modification methods to modify CaO powder, and prepares CaO modified powder with good water resistance, which solves the problems of difficulty in 3DP molding and powder denaturation of traditional CaO powder during printing. The present invention provides a feasible production method for 3DP manufacturing of CaO soluble ceramic cores, opening up a new direction for low-cost soluble ceramic core manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0052] Figure 1 The figure is a process flow diagram for preparing a soluble ceramic shell / core according to the present invention. DETAILED DESCRIPTION
[0053] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] The method for preparing the soluble ceramic shell / core provided in Example 1 of the present invention mainly comprises the following steps:
[0056] (1) 5 g of stearic acid and 95 g of anhydrous ethanol were mixed, heated in a water bath at 60°C for 2 h, and mixed to obtain a modified solution. 65 g of calcium oxide and 35 g of the modified solution were added to a ball mill, and then 8% of the raw material mass fraction of 1 mm diameter zirconium oxide ball milling beads were added, and ball milling was performed using a planetary ball mill for 12 h, and then the ball milled uniform slurry was dried at 50°C for 24 h, crushed and sieved through a 200 mesh screen to obtain a coarse modified calcium oxide powder.
[0057] Import the designed ceramic shell / core stl three-dimensional structure into the computer printing program, and adjust the printing parameters (printing layer height 0.15mm, binder saturation 80%), then spread the sieved modified calcium oxide powder on the powder feeding cylinder, place a ceramic pad and a stainless steel bottom plate on the surface of the working cylinder and spread the calcium oxide powder evenly. After starting printing, the nozzle starts to spray phenolic resin binder according to the path of the computer slice. After the nozzle completes one inkjet, the powder feeding cylinder and the working cylinder will rise and fall by one layer height respectively, and the powder spreading process is completed by the rotation and movement of the powder spreading roller, and the cycle is repeated to complete the entire ceramic shell / core printing process.
[0058] (2) After the printing is completed, the powder and the ceramic shell / core blank together with the stainless steel bottom plate are placed in a drying oven and heated and cured at 160°C. After curing for 4 hours, the drying oven is closed, and the stainless steel plate is taken out after cooling with the furnace. Next, the blank is taken out from the powder bed, and the residual powder on the ceramic shell / core blank is cleaned with a brush. Subsequently, the ceramic shell / core blank is placed in a basin, and a 20% nano ZrO2 ethanol dispersion is poured into it. The timing is started after all parts of the blank are completely impregnated. After 3 minutes, the impregnated ceramic shell / core blank is taken out and placed on a tray, placed in a drying oven at 60°C, and taken out after drying for 12 hours.
[0059] (3) The sintering of the ceramic shell / core blank is carried out by the buried firing method. 0.2 mm plate-shaped corundum powder is evenly spread on a ceramic plate specially used for sintering. Then the dried ceramic shell / core blank is placed on the ceramic plate. All parts of the blank are completely buried with plate-shaped corundum powder. Subsequently, it is placed in a high-temperature sintering furnace and sintered at 600 °C for 2 h, 1400 °C for 2 h, and a heating rate of 2 °C / min. Finally, the soluble ceramic shell / core is obtained by cooling in the furnace.
[0060] Example 2
[0061] The method for preparing the soluble ceramic shell / core provided in Example 2 of the present invention mainly comprises the following steps:
[0062] (1) 7 g of silane coupling agent and 93 g of acetone were mixed, heated in a water bath at 80°C for 2 h, and mixed to obtain a modified solution. 60 g of calcium oxide and 40 g of the modified solution were added to a ball mill, and then 10% of the raw material mass fraction of 1.5 mm diameter zirconium oxide ball milling beads were added, and ball milling was performed using a planetary ball mill for 10 h, and then the ball milled uniform slurry was dried at 55°C for 24 h, crushed and sieved through a 250 mesh screen to obtain a coarse modified calcium oxide powder.
[0063] Import the designed ceramic shell / core stl three-dimensional structure into the computer printing program, and adjust the printing parameters (printing layer height 0.10mm, binder saturation 120%), then spread the sieved modified calcium oxide powder on the powder feeding cylinder, place a ceramic pad and a stainless steel bottom plate on the surface of the working cylinder and spread the calcium oxide powder evenly. After starting printing, the nozzle starts to spray phenolic resin binder according to the path of the computer slice. After the nozzle completes one inkjet, the powder feeding cylinder and the working cylinder will rise and fall by one layer height respectively, and the powder spreading process is completed by the rotation and movement of the powder spreading roller, and the cycle is repeated to complete the entire ceramic shell / core printing process.
[0064] (2) After the printing is completed, the powder and the ceramic shell / core blank together with the stainless steel bottom plate are placed in a drying oven and heated and cured at 180°C. After curing for 4 hours, the drying oven is closed, and the stainless steel plate is taken out after cooling with the furnace. Next, the blank is taken out from the powder bed, and the residual powder on the ceramic shell / core blank is cleaned with a brush. Subsequently, the ceramic shell / core blank is placed in a basin, and a 20% nano-YiO2 ethanol dispersion is poured into it. The timing is started after all parts of the blank are completely impregnated. After 2.5 minutes, the impregnated ceramic shell / core blank is taken out and placed on a tray, placed in a drying oven at 80°C, and taken out after drying for 12 hours.
[0065] (3) The sintering of the ceramic shell / core blank is carried out by buried firing. 0.2 mm plate-shaped corundum powder is evenly spread on a ceramic plate specially used for sintering. Then the dried ceramic shell / core blank is placed on the ceramic plate. All parts of the blank are completely buried with plate-shaped corundum powder. Subsequently, it is placed in a high-temperature sintering furnace and sintered at 600 °C for 2 h, 1500 °C for 2 h, and a heating rate of 2 °C / min. Finally, the soluble ceramic shell / core is obtained by cooling in the furnace.
[0066] Example 3
[0067] The method for preparing the soluble ceramic shell / core provided in Example 3 of the present invention mainly comprises the following steps:
[0068] (1) 3 g of ethyl bromide and 97 g of acetone were mixed, heated in a water bath at 60°C for 2 h, and mixed to obtain a modified solution. 70 g of calcium oxide and 30 g of the modified solution were added to a ball mill, and then 8% of the raw material mass fraction of 0.8 mm diameter zirconium oxide ball milling beads were added, and ball milling was performed using a planetary ball mill for 12 h, and then the ball milled uniform slurry was dried at 60°C for 24 h, crushed and sieved through a 320 mesh screen to obtain a coarse modified calcium oxide powder.
[0069] Import the designed ceramic shell / core stl three-dimensional structure into the computer printing program, and adjust the printing parameters (printing layer height 0.12mm, binder saturation 100%), then spread the sieved modified calcium oxide powder on the powder feeding cylinder, place a ceramic pad and a stainless steel bottom plate on the surface of the working cylinder and spread the calcium oxide powder evenly. After starting printing, the nozzle starts to spray phenolic resin binder according to the path of the computer slice. After the nozzle completes one inkjet, the powder feeding cylinder and the working cylinder will rise and fall by one layer height respectively, and the powder spreading process is completed by the rotation and movement of the powder spreading roller, and the cycle is repeated to complete the entire ceramic shell / core printing process.
[0070] (2) After the printing is completed, the powder and the ceramic shell / core blank together with the stainless steel bottom plate are placed in a drying oven and heated and cured at 165°C. After curing for 3.5 hours, the drying oven is closed, and the stainless steel plate is taken out after cooling with the furnace. Next, the blank is taken out from the powder bed, and the residual powder on the ceramic shell / core blank is cleaned with a brush. Subsequently, the ceramic shell / core blank is placed in a basin, and a 15% nano ZrO2 ethanol dispersion is poured into it. The timing is started after all parts of the blank are completely impregnated. After 4 minutes, the impregnated ceramic shell / core blank is taken out and placed on a tray, placed in a drying oven at 50°C, and taken out after drying for 18 hours.
[0071] (3) The sintering of the ceramic shell / core blank is carried out by buried firing. 0.2 mm plate-like corundum powder is evenly spread on a ceramic plate specially used for sintering. Then the dried ceramic shell / core blank is placed on the ceramic plate. All parts of the blank are completely buried with plate-like corundum powder. Subsequently, it is placed in a high-temperature sintering furnace and sintered at 700 °C for 2 h, 1450 °C for 2 h, and a heating rate of 2.5 °C / min. Finally, the soluble ceramic shell / core is obtained by cooling in the furnace.
[0072] Example 4
[0073] The method for preparing the soluble ceramic shell / core provided in Example 4 of the present invention mainly comprises the following steps:
[0074] (1) 2 g of stearic acid and 98 g of anhydrous ethanol were mixed, heated in a water bath at 60° C. for 2 h, and mixed to obtain a modified solution. 30 g of calcium oxide and 70 g of the modified solution were added to a ball mill, and then 5% of the raw material mass fraction of 0.8 mm diameter zirconium oxide ball milling beads were added, and ball milling was performed using a planetary ball mill for 6 h, and then the ball milled uniform slurry was dried at 70° C. for 24 h, crushed and sieved through a 100-mesh sieve to obtain a coarse modified calcium oxide powder.
[0075] Import the designed ceramic shell / core stl three-dimensional structure into the computer printing program, and adjust the printing parameters (printing layer height 0.05mm, binder saturation 140%), then spread the sieved modified calcium oxide powder on the powder feeding cylinder, place a ceramic pad and a stainless steel bottom plate on the surface of the working cylinder and spread the calcium oxide powder evenly. After starting printing, the nozzle starts to spray phenolic resin binder according to the path of the computer slice. After the nozzle completes one inkjet, the powder feeding cylinder and the working cylinder will rise and fall by one layer height respectively, and the powder spreading process is completed by the rotation and movement of the powder spreading roller, and the cycle is repeated to complete the entire ceramic shell / core printing process.
[0076] (2) After the printing is completed, the powder and the ceramic shell / core blank together with the stainless steel bottom plate are placed in a drying oven and heated and cured at 150°C. After curing for 5 hours, the drying oven is closed, and the stainless steel plate is taken out after cooling with the furnace. Next, the blank is taken out from the powder bed, and the residual powder on the ceramic shell / core blank is cleaned with a brush. Subsequently, the ceramic shell / core blank is placed in a basin, and a 20% nano ZrO2 ethanol dispersion is poured into it. The timing is started after all parts of the blank are completely impregnated. After 3 minutes, the impregnated ceramic shell / core blank is taken out and placed on a tray, placed in a drying oven at 50°C, and taken out after drying for 24 hours.
[0077] (3) The sintering of the ceramic shell / core blank is carried out by the buried firing method. 0.2 mm plate-shaped corundum powder is evenly spread on a ceramic plate specially used for sintering. Then the dried ceramic shell / core blank is placed on the ceramic plate. All parts of the blank are completely buried with plate-shaped corundum powder. Subsequently, it is placed in a high-temperature sintering furnace and sintered at 600 °C for 3 h, 1300 °C for 3 h, and a heating rate of 1 °C / min. Finally, the soluble ceramic shell / core is obtained by cooling in the furnace.
[0078] Example 5
[0079] The method for preparing the soluble ceramic shell / core provided in Example 5 of the present invention mainly comprises the following steps:
[0080] (1) 8 g of stearic acid and 92 g of anhydrous ethanol were mixed, heated in a water bath at 60° C. for 2 h, and mixed to obtain a modified solution. 40 g of calcium oxide and 60 g of the modified solution were added to a ball mill, and then 15% of the raw material mass fraction of 2 mm diameter zirconium oxide ball milling beads were added, and ball milling was performed using a planetary ball mill for 12 h, and then the ball milled uniform slurry was dried at 100° C. for 6 h, crushed and sieved through a 500 mesh screen to obtain a coarse modified calcium oxide powder.
[0081] Import the designed ceramic shell / core stl three-dimensional structure into the computer printing program, and adjust the printing parameters (printing layer height 0.20mm, binder saturation 70%), then spread the sieved modified calcium oxide powder on the powder feeding cylinder, place a ceramic pad and a stainless steel bottom plate on the surface of the working cylinder and spread the calcium oxide powder evenly. After starting printing, the nozzle starts to spray phenolic resin binder according to the path of the computer slice. After the nozzle completes one inkjet, the powder feeding cylinder and the working cylinder will rise and fall by one layer height respectively, and the powder spreading process is completed by the rotation and movement of the powder spreading roller, and the cycle is repeated to complete the entire ceramic shell / core printing process.
[0082] (2) After the printing is completed, the powder and the ceramic shell / core blank together with the stainless steel bottom plate are placed in a drying oven and heated and cured at 180°C. After curing for 2 hours, the drying oven is closed, and the stainless steel plate is taken out after cooling with the furnace. Next, the blank is taken out from the powder bed, and the residual powder on the ceramic shell / core blank is cleaned with a brush. Subsequently, the ceramic shell / core blank is placed in a basin, and a 20% nano ZrO2 ethanol dispersion is poured into it. The timing is started after all parts of the blank are completely impregnated. After 30 seconds, the impregnated ceramic shell / core blank is taken out and placed on a tray, placed in a drying oven at 90°C, and taken out after drying for 8 hours.
[0083] (3) The sintering of the ceramic shell / core blank is carried out by burying the blank. 0.2 mm plate-shaped corundum powder is evenly spread on a ceramic plate specially used for sintering. Then the dried ceramic shell / core blank is placed on the ceramic plate. All parts of the blank are completely buried with plate-shaped corundum powder. Subsequently, the blank is placed in a high-temperature sintering furnace and sintered at 800 °C for 1 h, 1500 °C for 2 h, and a heating rate of 5 °C / min. Finally, the soluble ceramic shell / core is obtained by cooling in the furnace.
[0084] Example 6
[0085] The method for preparing the soluble ceramic shell / core provided in Example 6 of the present invention mainly comprises the following steps:
[0086] (1) 1 g of stearic acid and 99 g of anhydrous ethanol were mixed, heated in a water bath at 60°C for 2 h, and mixed to obtain a modified solution. 65 g of calcium oxide and 35 g of the modified solution were added to a ball mill, and then 8% of the raw material mass fraction of 1 mm diameter zirconium oxide ball milling beads were added, and ball milling was performed using a planetary ball mill for 12 h, and then the ball milled uniform slurry was dried at 50°C for 24 h, crushed and sieved through a 200 mesh screen to obtain a coarse modified calcium oxide powder.
[0087] Import the designed ceramic shell / core stl three-dimensional structure into the computer printing program, and adjust the printing parameters (printing layer height 0.15mm, binder saturation 80%), then spread the sieved modified calcium oxide powder on the powder feeding cylinder, place a ceramic pad and a stainless steel bottom plate on the surface of the working cylinder and spread the calcium oxide powder evenly. After starting printing, the nozzle starts to spray phenolic resin binder according to the path of the computer slice. After the nozzle completes one inkjet, the powder feeding cylinder and the working cylinder will rise and fall by one layer height respectively, and the powder spreading process is completed by the rotation and movement of the powder spreading roller, and the cycle is repeated to complete the entire ceramic shell / core printing process.
[0088] (2) After the printing is completed, the powder and the ceramic shell / core blank together with the stainless steel bottom plate are placed in a drying oven and heated and cured at 160°C. After curing for 4 hours, the drying oven is closed, and the stainless steel plate is taken out after cooling with the furnace. Next, the blank is taken out from the powder bed, and the residual powder on the ceramic shell / core blank is cleaned with a brush. Subsequently, the ceramic shell / core blank is placed in a basin, and a 20% nano ZrO2 ethanol dispersion is poured into it. The timing is started after all parts of the blank are completely impregnated. After 3 minutes, the impregnated ceramic shell / core blank is taken out and placed on a tray, placed in a drying oven at 60°C, and taken out after drying for 12 hours.
[0089] (3) The sintering of the ceramic shell / core blank is carried out by the buried firing method. 0.2 mm plate-shaped corundum powder is evenly spread on a ceramic plate specially used for sintering. Then the dried ceramic shell / core blank is placed on the ceramic plate. All parts of the blank are completely buried with plate-shaped corundum powder. Subsequently, it is placed in a high-temperature sintering furnace and sintered at 600 °C for 2 h, 1400 °C for 2 h, and a heating rate of 2 °C / min. Finally, the soluble ceramic shell / core is obtained by cooling in the furnace.
[0090] Example 7
[0091] The method for preparing the soluble ceramic shell / core provided in Example 1 of the present invention mainly comprises the following steps:
[0092] (1) 10 g of stearic acid and 90 g of anhydrous ethanol were mixed, heated in a water bath at 60°C for 2 h, and mixed to obtain a modified solution. 65 g of calcium oxide and 35 g of the modified solution were added to a ball mill, and then 8% of the raw material mass fraction of 1 mm diameter zirconium oxide ball milling beads were added, and ball milling was performed using a planetary ball mill for 12 h, and then the ball milled uniform slurry was dried at 50°C for 24 h, crushed and sieved through a 200 mesh screen to obtain a coarse modified calcium oxide powder.
[0093] Import the designed ceramic shell / core stl three-dimensional structure into the computer printing program, and adjust the printing parameters (printing layer height 0.15mm, binder saturation 80%), then spread the sieved modified calcium oxide powder on the powder feeding cylinder, place a ceramic pad and a stainless steel bottom plate on the surface of the working cylinder and spread the calcium oxide powder evenly. After starting printing, the nozzle starts to spray phenolic resin binder according to the path of the computer slice. After the nozzle completes one inkjet, the powder feeding cylinder and the working cylinder will rise and fall by one layer height respectively, and the powder spreading process is completed by the rotation and movement of the powder spreading roller, and the cycle is repeated to complete the entire ceramic shell / core printing process.
[0094] (2) After the printing is completed, the powder and the ceramic shell / core blank together with the stainless steel bottom plate are placed in a drying oven and heated and cured at 160°C. After curing for 4 hours, the drying oven is closed, and the stainless steel plate is taken out after cooling with the furnace. Next, the blank is taken out from the powder bed, and the residual powder on the ceramic shell / core blank is cleaned with a brush. Subsequently, the ceramic shell / core blank is placed in a basin, and a 20% nano ZrO2 ethanol dispersion is poured into it. The timing is started after all parts of the blank are completely impregnated. After 3 minutes, the impregnated ceramic shell / core blank is taken out and placed on a tray, placed in a drying oven at 60°C, and taken out after drying for 12 hours.
[0095] (3) The sintering of the ceramic shell / core blank is carried out by the buried firing method. 0.2 mm plate-shaped corundum powder is evenly spread on a ceramic plate specially used for sintering. Then the dried ceramic shell / core blank is placed on the ceramic plate. All parts of the blank are completely buried with plate-shaped corundum powder. Subsequently, it is placed in a high-temperature sintering furnace and sintered at 600 °C for 2 h, 1400 °C for 2 h, and a heating rate of 2 °C / min. Finally, the soluble ceramic shell / core is obtained by cooling in the furnace.
[0096] Comparative Example 1
[0097] Step (1) in Example 1 was replaced by directly ball-milling 65 g of calcium oxide and anhydrous ethanol using a planetary ball mill for 12 h, and sieving through a 200-mesh screen to obtain calcium oxide powder, which was printed using the printing method in Example 1, and the remaining preparation steps were the same as those in Example 1. Since calcium oxide was not modified using a modifying solution, when calcium oxide was directly printed, the printing was agglomerated, and the ceramic shell / core blank could not be effectively printed.
[0098] Comparative Example 2
[0099] The step (1) in Example 1, "mixing 5 g of stearic acid and 95 g of anhydrous ethanol" was replaced by "mixing 0.8 g of stearic acid and 99.2 g of anhydrous ethanol", and the remaining preparation steps were the same as those in Example 1. Compared with Example 1, due to the small amount of stearic acid added, when the modified calcium oxide prepared by this scheme was printed, there was still a relatively obvious agglomeration phenomenon due to the small amount of stearic acid covering the surface of the calcium oxide powder, resulting in the inability to effectively print the ceramic shell / core blank.
[0100] Comparative Example 3
[0101] The step (1) in Example 1 in which "5 g of stearic acid and 95 g of anhydrous ethanol are mixed" is replaced by "11 g of stearic acid and 89 g of anhydrous ethanol are mixed", and the remaining preparation steps are consistent with those in Example 1. Compared with Example 1, since the content of stearic acid is high enough and the specific surface area of the calcium oxide powder is constant, the increase in the content of stearic acid has little effect on the contact angle of the modified calcium oxide powder, and the final printing effect is slightly different from the sample in Example 1, and the porosity of the ceramic core finally printed is slightly lower.
[0102] Test Example
[0103] Porosity test
[0104] For the molded samples prepared in Examples 1, 6, 7 and Comparative Examples 1 to 3, the contents of different modifiers and the corresponding adjusted modified solvents were used to prepare the initial blanks (4 groups of parallel test blank samples were prepared for the samples with the same stearic acid content), and the porosity of the prepared soluble ceramic shell / core products was tested. The data obtained are shown in Table 1 below.
[0105] Table 1: Porosity of samples with different stearic acid contents.
[0106]
[0107] As shown in Table 1, 4 groups of parallel experiments were carried out on molded samples with different contents. The modifier in Examples 1, 6 and 7 was stearic acid. The porosity of the samples in Examples 1, 6, 7 and Comparative Examples 1, 2 and 3 were compared. When the amount of the modifier was 1 to 10 parts by mass, the porosity of the prepared samples could meet the requirements.
[0108] The porosity of the samples in Comparative Example 2 was compared with that in Example 1. Since the amount of stearic acid used in Comparative Example 2 was relatively small, when the prepared modified calcium oxide was printed, there was still a relatively obvious agglomeration phenomenon due to the small amount of stearic acid covering the surface of the calcium oxide powder. As a result, the ceramic shell / core blank could not be effectively printed, and the porosity could not be measured.
[0109] The porosity of the samples in Comparative Example 3 is compared with that in Example 1. Since the content of stearic acid is high enough and the specific surface area of the calcium oxide powder is constant, the increase in the content of stearic acid has little effect on the contact angle of the modified calcium oxide powder. The final printing effect is slightly different from the sample in Example 1, and the porosity of the ceramic core finally printed is slightly lower.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a soluble ceramic shell / core, characterized in that: The preparation method comprises the following steps: Step S1: ball-milling, drying, and sieving the raw materials containing calcium oxide and modified solution to obtain modified calcium oxide powder; Step S2: printing the modified calcium oxide powder into a ceramic shell / core blank, heating and curing, infiltration, and drying to obtain a ceramic shell / core blank; Step S3: sintering the ceramic shell / core blank to obtain the soluble ceramic shell / core.
2. The preparation method according to claim 1, characterized in that In the step S1, the modified solution includes a modifying agent and a modifying solvent; The modifier is selected from at least one of ethyl bromide, benzene bromide, a silane coupling agent, stearic acid, and n-octadecyltrichlorosilane; The modified solvent is selected from at least one of methanol, ethanol, glycerol and acetone.
3. The preparation method according to claim 2, characterized in that: Calculated by weight, the amount of the modifier is 1 to 10 parts, and the amount of the modified solvent is 99 to 90 parts.
4. The preparation method according to claim 1, characterized in that: In the step S1, the amount of calcium oxide used is 30 to 70 parts by mass, and the amount of the modified solution used is 70 to 30 parts by mass.
5. The preparation method according to claim 1, characterized in that: In the step S1, the ball milling time is 6 to 12 hours; During the ball milling, the diameter of the grinding balls is 0.8 to 2 mm; During the ball milling, the mass fraction of the grinding balls is 5 to 15% of the raw material; The drying temperature is 50-100°C, and the drying time is 6h-24h; When sieving after drying, the mesh number of the sieve is 100 to 500 meshes.
6. The preparation method according to claim 1, characterized in that: In the step S2, the temperature of the heating and curing is 150°C to 180°C, and the time of the heating and curing is 2h to 5h; The drying temperature is 50°C to 90°C, and the drying time is 8h to 24h; The impregnation time is 30s to 3min; In the step S2, the impregnation liquid used in the impregnation is at least one selected from nano-SiO2 ethanol dispersion, nano-ZrO2 ethanol dispersion, and nano-YiO2 ethanol dispersion.
7. The preparation method according to claim 1, characterized in that: In step S2, the printed layer height is 0.05 mm to 0.20 mm; The printed adhesive is phenolic resin, and the saturation of the adhesive is 70% to 140%.
8. The preparation method according to claim 1, characterized in that: In the step S3, the sintering includes a first sintering and a second sintering; The temperature of the first sintering is 600° C. to 800° C., and the time of the first sintering is 1 h to 3 h; The second sintering temperature is 1300°C to 1500°C, and the second sintering time is 2h to 3h; The heating rate of the sintering is 1-5°C / min.
9. The soluble ceramic shell / core prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the soluble ceramic shell / core in casting structure according to claim 9, characterized in that: The material of the cast structure is selected from at least one of cast iron, cast steel, aluminum alloy, titanium alloy and magnesium alloy.
Citation Information
Patent Citations
Fast manufacturing method for powder-coated and calcium-oxide-based ceramic mould
CN106079030A
Layer-by-layer self-assembled calcium oxide microcapsule as well as preparation method and application thereof
CN114736665A
Calcium oxide-based ceramic core rapidly formed based on micro-extrusion 3D printing technology and preparation method of calcium oxide-based ceramic core
CN115583831A
Soluble ceramic shell or ceramic core material and preparation method and application thereof
CN115673241A
Preparation method of calcium oxide ceramic core
CN117362004A